Biomass supply chain optimization : consideration of underutilised biomass via element targeting approach - Lim, Chun Hsion (2016)
Achieving a sustainable process system is one of the main focuses in research and development throughout the world. Development in renewable resources is at the peak to replace and reduce the usage of fossil fuel in chemical and energy production. Bio-resources have shown great potential to accomplish a sustainable system, especially bio-waste which also known as biomass, to avoid interruption of food supplement within the supply chain network. However, worldwide implementation of biomass-based process technology is yet to be feasible due to high logistic cost, complexity of biomass properties, fluctuation of biomass availability, and relatively low conversion rate in biomass conversion technologies. Unique regional biomass system further creates research gaps as researches are conducted independently to only focus on specific biomass species available within the region. This raises issue of underutilisation of biomass where biomasses value are not used in the full potential, or ignorance of certain species of biomass (such as food waste, fruit shells and energy crop) in research development.